The Role Of The School Environment In Shaping Students' Moral Character At State High School - Maknunatul Hikmah; Rifa'i Rifa'i (Universitas Nurul Jadid, 2026)
This study aims to examine the role of the school environment in shaping students’ moral character through educational interactions. It employs a qualitative approach with a case study design to explore interaction patterns within a specific school context in depth. The research subjects included 10th-grade students, Islamic Religious Education teachers, guidance and counseling teachers, and homeroom teachers. Data were collected through in-depth interviews, participatory observation, and documentation. The analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that educational interactions play a central role in shaping students’ moral character. Classroom interactions serve not only as a medium for knowledge transfer but also as a strategic space for internalizing values such as discipline, responsibility, and mutual respect. Interactions outside the classroom, including extracurricular activities and religious practices, further strengthen character development. In addition, peer interactions contribute to the formation of social awareness and positive behavior through dynamic social influence. The novelty of this study lies in its integrative analysis of multi-contextual educational interactions, encompassing classroom, extracurricular, religious, and peer environments as a unified system in character formation. This study highlights the synergistic relationship among these interaction domains within the school ecosystem. Thus, a conducive school environment, supported by teachers’ exemplary behavior and positive social interactions, becomes a key determinant in shaping students’ moral character.